Complex Mechanism of Interaction in the «School-University» System: Approaches to Performance Assessment - Nadezhda V. KAPUSTINA; Evgeniya K. KARPUNINA; Navai N. RUSTAMOV; Anastasia A. YUSSUF; Irada T. RUSTAMOVA (Communications of International Proceedings, 2020)
Effective interaction of all subjects of the educational services market in terms of economic transformation remains an important issue on the agenda, especially during the development of new technologies and teaching methods. Accordingly, the formation of mechanisms that increase the effectiveness of organizations in the field of education is a very difficult task. The aim of the research is to develop methodological approaches to the formation of an effective integrated mechanism of interaction in the school-University system. To achieve this goal, the main factors influencing the interaction process were identified and grouped, approaches to evaluating the performance of the University depending on the goal were clarified, as well as a methodological approach to the formation of a comprehensive mechanism for interaction between the school-University system was proposed. The proposed mechanism of complex interaction in the school-University system can be adapted for any educational institution, and has shown its effectiveness in the process of testing in one of the educational institutions. Research methods: analysis and synthesis, method of constructing hierarchies, economic and statistical, dynamic, situational analysis, tabular interpretation of statistical information.
Keywords: Economic Efficiency; Assessment Methods; School-University Interaction; System Approach